Research on the filed commissioning test method for phase selection making control device - Chen Xiangyi; Zhen Wei; Liu Mingzhong; Li Chunyan (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
The U/EHVDC technology plays an important rule for transmitting from West to East in China. In order to improve the reliability of electrical equipments in Ultra High Voltage Direct Current (UHVDC) transmission project, and standardize the filed test method, the field commissioning test technology of phase selection making control device is studied combining Xiangshang ±800kV UHVDC transmission project. From the principle of work of phase selection making control device, according to the pre-breakdown features and impact of environmental temperature and control voltage, the closing time model of typical breaker applied to the detection for phase selection making control device is established, and the method for filed commissioning test is proposed. At last, the filed commissioning test technology is applied in Fulong converter station, the testing results show that it could find and eliminate the equipment deficiency timely, which verify its feasibility and validity.